The price of fringe benefits when formal and informal labor markets coexist - David Argente; Jorge García (IZA Journal of Labor Economics, 2015)
We use the Mexican labor market structure to price the set of fringe benefits that household heads receive when formally employed. We exploit longitudinal, nationally-representative information on household heads who are formal, informal, or switch status at least once in our data. Using monthly labor income and an efficient markets hypothesis, we identify a standard linear model which accounts for time-variant household heads' characteristics and household level and time fixed effects. Under the usual strict-exogeneity assumption, we find that the price of fringe benefits is approximately 7.9% of the average monthly labor income of informal workers, or 217 USD.
Keywords: D4; J3; J4; 330; Dual labor market; Fringe benefits; Informal labor market